2008
DOI: 10.1585/pfr.3.s1074
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Energetic Ion Transport due to Alfvén Eigenmodes in LHD Plasma

Abstract: The creation of holes and clumps in an energetic ion energy spectrum associated with Alfvén eigenmodes was examined using the neutral particle analyzer (NPA) on the LHD shot #47645. The difference in slowingdown times between the holes and clumps suggested that the energetic ions were transported over 10% of the plasma minor radius. The spatial profile and frequency of the Alfvén eigenmodes were analyzed with the AE3D code. The phase space structures of the energetic ions on the NPA line-of-sight were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The maximum amplitude is v r =v A $ 2-3 Â 10 À3 for both the fluctuations, which is comparable to those inferred for the fast ion transport suggested by the NPA measurement. 15,17 The fast ion pressure profiles are compared between before and after the AE burst in Fig. 7.…”
Section: A Global Alfv En Eigenmode (Gae) and Taesmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum amplitude is v r =v A $ 2-3 Â 10 À3 for both the fluctuations, which is comparable to those inferred for the fast ion transport suggested by the NPA measurement. 15,17 The fast ion pressure profiles are compared between before and after the AE burst in Fig. 7.…”
Section: A Global Alfv En Eigenmode (Gae) and Taesmentioning
confidence: 99%
“…The AEs observed in the LHD experiment were analyzed using the AE3D code, 14 and even and odd toroidal Alfv en eigenmodes (TAEs) were found for the candidates for the AEs at the bursts. 15 Reduced simulations, where the spatial profiles and the frequencies of the AEs are given by the AE3D code and fixed in the simulations, demonstrate that the AE bursts take place recurrently with neutral beam injection (NBI) and collisions. 16,17 The amplitude of the a) todo@nifs.ac.jp MHD velocity v and the magnetic fluctuation dB that is consistent with the beam ion transport over 10% of the minor radius were investigated and found to be of the order of v=v A $ dB=B $ 10 À3 , where v A and B are the Alfv en velocity and the magnetic field at the plasma center, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A numerical simulation was conducted to analyze the LHD NPA data shown in Fig. 10 (d) by using a hybrid code that solves the MHD fluid and drift kinetic equations assuming an axisymmetric equilibrium comparable to that of the LHD [60]. It revealed that the radial excursion of energetic ions by each TAE burst reaches about 10% of the minor radius, as inferred from the experimental data.…”
Section: Effects Of Taes On Energetic Ion Transport In Lhdmentioning
confidence: 89%
“…A new NPA with further high time response is under development to clarify the details of the nonlinear processes in real and phase spaces [49]. A first trial of numerical simulation using a hybrid code where MHD fluid and drift kinetic equations are solved has demonstrated that the radial excursion of energetic ions by each TAE burst reaches about 10% of the minor radius if the internal magnetic fluctuation amplitude is in the order of 10 −3 B t [50]. More advanced simulation is being developed for detailed understanding of the above-mentioned process.…”
Section: Anomalous Redistribution/loss Of Energetic Ions By Various Mmentioning
confidence: 99%